2016
DOI: 10.3171/2015.7.spine1534
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical comparison of 3 different posterior fixation techniques for 2-level lumbar spinal disorders

Abstract: OBJECT This study sought to make a biomechanical comparison of 3 different posterior fixation techniques for 2-level lumbar spinal disorders. METHODS Eight fresh-frozen human cadaver lumbar spines (4 from L-1 to L-5, 4 from L-1 to S-1) were tested by applying pure moments of ± 8 Nm. Each specimen was first tested intact, and then the left facetectomies of L3–4 and L4–5 were performed to establish an unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Accordingly, several modified techniques have been assessed by finite element analysis and biomechanical tests, for example, unilateral pedicle screw (UPS), UPS with contralateral translaminar facet joint screw (UPS þ TFS) and etc. The results show that the stability of UPS þ TFS is similar to that of BPS for both 1-level and 2-level lumbar spinal disorders [5][6][7]. Moreover, some recent clinical studies also indicate TLIF using UPS þ TFS by paramedian mini-incision is a safe, feasible and effective method to treat one or two segment lumbar degenerative disorders [8,9].…”
Section: Introductionmentioning
confidence: 71%
“…Accordingly, several modified techniques have been assessed by finite element analysis and biomechanical tests, for example, unilateral pedicle screw (UPS), UPS with contralateral translaminar facet joint screw (UPS þ TFS) and etc. The results show that the stability of UPS þ TFS is similar to that of BPS for both 1-level and 2-level lumbar spinal disorders [5][6][7]. Moreover, some recent clinical studies also indicate TLIF using UPS þ TFS by paramedian mini-incision is a safe, feasible and effective method to treat one or two segment lumbar degenerative disorders [8,9].…”
Section: Introductionmentioning
confidence: 71%
“…They concluded that UPS with contralateral TLS has superior flexion-extension and lateral bending compared with UPS but inferior lateral bending compared with bilateral pedicle screw. 53 However, Zhan et al 54 tested 12 fresh human cadavers, and found that both pedicle screw and TLS significantly reduced range of motion and increased stiffness compared with intact spine, and there is no significant difference in stability between the 2 constructs.…”
Section: Biomechanicsmentioning
confidence: 99%
“…In the lumbar spine, Liu et al 53 compared the biomechanical properties of 3 posterior constructs, unilateral pedicle screw (UPS) versus UPS with contralateral TLS versus bilateral pedicle screw. They concluded that UPS with contralateral TLS has superior flexion-extension and lateral bending compared with UPS but inferior lateral bending compared with bilateral pedicle screw.…”
mentioning
confidence: 99%
“…This approach is widely popular for single and multilevel spinal fusions for various lumbar disorders. Several posterior fixation techniques are currently available to promote spinal fusion with bilateral fixation being considered the “gold standard” [ 1 ]. This is a result of its ability to improve arthrodesis rates, increase fusion, and prevent nonunion.…”
Section: Introductionmentioning
confidence: 99%